Early change in faecal calprotectin predicts primary non-response to anti-TNFα therapy in Crohn's disease. (1st December 2016) - Pavlidis, Polychronis; Gulati, Shraddha; Dubois, Patrick; Chung-Faye, Guy; Sherwood, Roy; Bjarnason, Ingvar; Hayee, Bu'Hussain
Abstract: Objective: The early identification of primary non-response to anti-TNFα therapy facilitates the timely management of patients with Crohn's disease (CD). A recent, pilot study to detect prognostic markers of early response to anti-TNFα therapy identified the two genes coding for the calprotectin subunits (S100A8, S100A9) to be among the most highly expressed gene transcripts in non-responders. This study tests the hypothesis that measurements of faecal calprotectin (FCAL) pre- and post-anti-TNFα induction can predict primary non-response. Methods: Retrospective study of 32 CD patients treated over a two-year period. Outcomes were assessed at 6 months based on clinical activity scores and the use of corticosteroids: (a) remission: Harvey–Bradshaw index (HBI) < 5, off corticosteroids >2 months; (b) response: drop in HBI >3, off corticosteroids; (c) non-response: ΔFCAL (and ΔCRP, respectively) was calculated as (FCAL post-induction – FCAL pre-induction) × 100/FCAL pre induction. Results: At 6 months, 23 (72%) patients had responded (median (interquartile range) HBI: 4 (3–5), FCAL: 55 (27–146)), 17 (73%) of whom were in remission [HBI: 3 (2.5–4) and FCAL: 42 (16–115)]. There was a significant difference in the ΔFCAL from baseline to post-induction in the three groups ( p  < 0.0001). Comparing non-responders to combined response and remission groups, the AUC of ΔFCAL to predict outcome at 6 months was 0.97. Using ROC analysis, a Δ70% returned a sensitivity and specificity of 99% and 96%, respectively (likelihood ratio, LR= 23). ΔCRP did not predict 6 months outcomes. Conclusions: A drop in FCAL <70% after induction predicts primary non-response to anti-TNFα in CD.